Enhancement of informed consent quality - Gómez Ramos, María Jesús; González Valverde, Francisco Miguel (Acta Bioethica, 2012)
Aim: To apply an enhancement circle for informed consent for transfusion of blood derivatives. Patients and Method: During 10 months 577 intervened patients were included in General Hospital Reina Sofia of Murcia, Spain. Six criteria were selected related to compliance with transfusion norms. After quality analysis, corrected measures were taken and the criteria were re evaluated. Data were compared with standards in both periods and between periods. In the first evaluation a poor compliance to criteria was observed. Based on the analysis of factors associated to lack of compliance and the resulting priorization from Pareto’s diagram, the intervention plan was divided in teaching activity and management modifications. Results: all criteria were under the standard (p<0.001). In the second evaluation, compliance for all criteria was significantly enhance with respect to the first; but nevertheless, results continue, also significantly, under established standards. Conclusions: Compliance to the six criteria was minimum at the beginning of the study; corrected measures were adequate, since they enhance all of them in the second evaluation, but it is necessary to insist in these measures since we continue under the established standard.